Early recognition is important when multiple magnets masquerade as a single chain after foreign body ingestion - Auriel August; Claudia Mueller (Elsevier, 2016)
Ingestions of multiple magnets can lead to serious damage to the gastrointestinal tract. Moreover, these foreign bodies can take deceptive shapes such as single chains which may mislead clinicians. We report the case of a ten-year-old boy who swallowed 33 magnets, the most yet reported, which took on the appearance of a single loop in the stomach, while actually being located in the stomach, small bowel, and colon. Early recognition and prompt intervention are necessary to avoid complications of this foreign body misadventure.